Pheidole (Hymenoptera, Formicidae) of Middle American Wet Forest - Longino, John T. (Zootaxa, 2019)
The ant genus Pheidole is a highly diverse lineage of ants that are dominant elements of tropical and subtropical ecosystems throughout the world. Biodiversity inventory projects in Middle American wet forests (southern Mexico to Costa Rica, lowland rainforest to high montane forest) allow an improved taxonomy of the genus in this region. An identification guide to 234 species in the region is provided, using a "bird guide" approach. Species are arranged in order of minor worker head width and scape length, and each species has a fixed layout that includes habitat and microhabitat information, standard views (minor lateral, minor face, major face), and a distribution map. The following new synonyms are proposed: biconstricta Mayr 1870 (= inermis Mayr 1870), carapuna Mann 1916 (= tristicula Wilson 2003), fimbriata Roger 1863 (= soesilae Makhan 2007), insipida Forel 1899 (= fariasana Wilson 2003, mooreorum Wilson 2003), longiscapa Forel 1901 (= cocciphaga Borgmeier 1934), plebecula Forel 1899 (= perdiligens Wilson 2003, texticeps Wilson 2003), nitidicollis Emery 1896 (= chalcoides Wilson 2003), nubicola Wilson 2003 (= cielana Wilson 2003, petrensis Wilson 2003), simonsi Wilson 2003 (= arctos Wilson 2003, gangamon Wilson 2003, thrasys Wilson 2003), striaticeps Mayr 1870 (= chloe Forel 1908), transversostriata Mayr 1887 (= scalaris Wilson 2003), vafra Santschi 1923 (= laticornis Wilson 2003). The following 57 new species are described: ajaxigibba, andersoni, angustinigra, atitlana, balatro, belonorte, besalon, bicornisculpta, brownampla, cahui, caliginosa, carinitida, corniclypeus, costaricensis, cusuco, depressinoda, eosimilis, familiaparra, fincanaranjo, hansoni, hectornitida, hitoy, huarache, imbrilis, indagarama, kasparii, kelainos, lagunculiminor, lamancha, laselvoides, lineafrons, luteagossamer, machaquila, marmor, moskitia, muralla, musacolor, musinermis, natalie, nephele, obturaculum, passivaeferox, perissothrix, platyscapa, probolonotum, rima, rogeripolita, savegre, sensipelada, sepultura, tapanti, tikal, tinamu, tsontekonwei, tuculutan, xiloa, zannia.